Alexander Charles Aviugana (1945-1994) - Beck, Tom (ARCTIC, 1994)
On May 1994, Arctic Canada lost a highly respected resident with the death of Alex Aviugana, age 49. Following a lengthy illness fought with selflessness and stoicism, Alex died in Inuvik, comforted by his wife Lena, their family, and close friends. Alex was born in the Mackenzie Delta near Aklavik and attended school at the Roman Catholic Mission in Aklavik for nine years, followed by high school in Inuvik. Alex's occupation as a hunter and trapper formed the basis for a deeply rooted sense of values that was successfully applied to the many roles and responsibilities he undertook on behalf of Inuvialuit society and Canada. Alex served with distinction on various Inuvialuit organizations including directorships with the Inuvialuit Regional Corporation, Inuvialuit Development Corporation, and the Inuvialuit Land Administration. He served as chairman and director of the Inuvik Community Corporation and the Hunters and Trappers Committee, director and chairman of the Inuvialuit Game Council, director of Umayot Corporation, as a valued member of the Fisheries Joint Management Committee since 1986, and a member of the Alaska/Inuvialuit Beluga Whale Committee. These roles encompassed a spectrum spanning economics to environmental protection and enabled Alex to perform a pivotal role in ensuring that the intent of the Inuvialuit Final Agreement, signed in 1984, was diligently pursued. The Mackenzie Delta-Beaufort Sea Regional Land Use Planning Commission was established in 1987, with Alex as its chairman. With Alex's leadership, the Commission set what has since been described as a world-class standard for community-based planning. It is worth noting that this was the broadest, if not the first, formal cooperative effort involving both Gwich'in and Inuvialuit society. The resulting land-use plan has since become a basic reference against which other development proposals are measured. .